ASSESSMENT OF SCHEDULE UNCERTAINTY AND RISK MITIGATION IN ACCELERATED BRIDGE CONSTRUCTION USING PERT - Alfandi Rizki Pratama Rolobessy; Ludfi Djakfar; Kartika Puspa Negara (LPPM Universitas Negeri Jakarta, 2025)
Traffic congestion is a critical issue in Indonesia’s rapidly urbanizing areas, particularly in regions with high vehicle density such as East Java. To address this, the construction of the Djuanda Flyover in Sidoarjo was initiated as a National Strategic Project (PSN) to alleviate bottlenecks along the Surabaya–Sidoarjo corridor. This study aims to evaluate the probability of successful schedule acceleration in the Djuanda Flyover project using the Program Evaluation and Review Technique (PERT). The research employs a mixed-methods approach, combining quantitative data from weekly and monthly progress reports and PERT-based estimations, with qualitative inputs from expert questionnaires involving 22 project stakeholders, including the owner (BBPJN Jawa-Bali), supervisory consultants, and contractors (PT Wika-Nindya KSO). The analysis focused on the critical path of the project, applying three-point estimates (optimistic, most likely, pessimistic) for activity durations. The initial duration was estimated at 102 days. After applying PERT analysis, the duration was reduced to approximately 95.32 days. With this acceleration, the probability of meeting the 98-day target completion date is 64.8%. These findings reveal a significant risk of failure to meet the targeted acceleration, suggesting the need for enhanced risk mitigation strategies and improved scheduling reliability. The study contributes to infrastructure project management literature by demonstrating how PERT can quantify schedule uncertainty in strategic national infrastructure projects. Recommendations include refining expert judgment techniques, optimizing resource allocation, and implementing real-time performance monitoring to increase schedule confidence beyond 90%. This research may serve as a reference for future accelerated infrastructure projects under similar constraints.